Jejunal and Multiple Mesenteric Calcifying Fibrous Pseudotumor Induced Jejunojejunal Intussusception - Hung-Hua Liang (Journal of the Formosan Medical Association, 2007)
We describe here a patient with an unusual presentation-mesenteric calcifying fibrous pseudotumor in association with jejunojejunal intussusception. This 25-year-old woman came to our emergency department with severe abdominal distension and intermittent epigastric cramping pain. She was found to have rebound tenderness and an ill-defined mass palpable in her lower abdomen. Abdominal computed tomography revealed an inhomogeneous soft tissue mass with target sign and intussusception of small intestine was suspected. Emergency laparotomy showed jejunojejunal intussusception involving ∼30 cm of jejunum with multiple tumors on the mesentery surface extending over the whole bowel mesenteric and peritoneal surfaces. One of the mesenteric tumors formed the leading point of the intussusception. Segmental resection of jejunum with primary anastomosis was done. Some larger tumors were resected but most of the other tumors were left in place because they were small and numerous and total resection was impossible. Pathology confirmed that the lesions were benign mesenteric calcifying fibrous pseudotumors. In such patients, surgery might be curative. If a large segment of the bowel is affected by calcifying fibrous pseudo-tumor, smaller pseudotumors might be left in place because these tend to be asymptomatic. But they might become the leading points of recurrent intussusception.